2020
DOI: 10.1002/brb3.2014
|View full text |Cite
|
Sign up to set email alerts
|

A cross‐sectional survey on occupational stress and associated dyslipidemia among medical staff in tertiary public hospitals in Wenzhou, China

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 29 publications
2
7
0
Order By: Relevance
“…This is why OS has started to receive a lot of attention from researchers. In this study, OS was found to be a risk factor for dyslipidemia in coal miners by logistic regression analysis, which is consistent with the conclusions reached by some researchers 28,29 . The mechanism by which OS affects lipid metabolism has not been elucidated, and two hypotheses are mainly considered.…”
Section: Discussionsupporting
confidence: 93%
“…This is why OS has started to receive a lot of attention from researchers. In this study, OS was found to be a risk factor for dyslipidemia in coal miners by logistic regression analysis, which is consistent with the conclusions reached by some researchers 28,29 . The mechanism by which OS affects lipid metabolism has not been elucidated, and two hypotheses are mainly considered.…”
Section: Discussionsupporting
confidence: 93%
“…A large number of studies have examined dyslipidemia in different occupations. Similarly, high levels of occupational stress in another study related to the medical staff were associated with an increased risk of dyslipidemia 33 . Zhang et al34 found a positive and nonlinear exposure-response relationship between occupational noise exposure and dyslipidemia.…”
Section: Discussionmentioning
confidence: 92%
“…Similarly, high levels of occupational stress in another study related to the medical staff were associated with an increased risk of dyslipidemia. 33 Zhang et al34 found a positive and nonlinear exposure-response relationship between occupational noise exposure and dyslipidemia. In addition, chronic exposure to lead can alter some liver enzymes, lipid profile, and lipoprotein levels.…”
Section: Discussionmentioning
confidence: 98%
“…This might be due to the improved healthcare system, working hours, less work stress, and to the organizational support system. Another study done in china 42 related to occupational stress and dyslipidemia among medical staff, where OSI-R data shows a clear difference in job stress between doctors and nurses. Doctors scored higher on the ORQ and PSQ questionnaires compared with nurses, and male staff had higher mean scores in ORQ and PSQ but a lower score in PRQ compared to female staff.…”
Section: Discussionmentioning
confidence: 99%